Nasopharyngeal cancer in Malaysia : Perceived severity, susceptibility and barriers in risk messages - Jia Yiing, Ho; Ting, Su Hie; Yuwana, Podin (Human Behavior, Development and Society, 2022)
Perceived severity and susceptibility of breast and lung cancers have been extensively studied but perceptions of the threat posed by nasopharyngeal cancer (NPC) is little understood. In this study perceptions were examined regarding the severity and susceptibility to NPC and barriers in taking preventive measures before and after reading specific cancer risk messages. The sample consisted of 65 participants living in the Kuching and Samarahan divisions of Sarawak, Malaysia who had not been diagnosed with NPC. Participants were interviewed about their perceived severity, susceptibility, and barriers towards the cancer before and after reading the NPC pamphlet, produced by the Ministry of Health, Malaysia. A total of 87.7% of participants perceived NPC as a severe disease, as it connotes death, scary symptoms, and disruption to the quality of life. Only 27.7% of participants believed that they were at risk of contracting NPC after reading the pamphlet. The common perceived risk factors were smoking, polluted environment, preserved food, and high NPC incidences in Malaysia. As for perceived barriers, 19% participants reported that living a healthy lifestyle would be hard, while 31% were fearful of screening. The study showed that the risk messages provided participants with more specific and accurate information on NPC.